RELASI MUSIK DAN SAWER DALAM PERTUNJUKAN DANGDUT NEW MONATA - Satria Rizky Utama; aris setiawan (Institut Seni Indonesia Padangpanjang, 2024)
This research is motivated by sawer activities in the New Monata dangdut music performance space. Sawer and dangdut music have a close relationship as performing arts. What we want to explain in this article is how saweran occurs in New Monata dangdut music performances and what the relationship is between music and saweran activities. This research was conducted using qualitative methods with stages of observation, interviews, document study, data presentation, data analysis, and drawing conclusions. Based on the analysis, it was found that the saweran activity in the New Monata dangdut music performance was carried out during the song. The act of nyawer is a reflective (spontaneous) and non-reflective (planned) action of the audience. Sawer is part of the reaction to the action of New Monata's dangdut music presentation. The relationship between music and sawer is a cause and effect relationship. The action of New Monata's dangdut music is the cause, the audience's reaction is the effect. Action and reaction are a natural phenomenon in a dangdut performance, music as action, and sawer as reaction.